Survey dataset on student perceptions and experiences of quality assurance in Vietnamese universities - Hien Thi Thu Ta; Cuong Huu Nguyen; Hung Thai Le; Nhung Thi Tuyet Pham; Huong Thi Pham; Nhung Thi Trinh (Data in Brief, 2023)
This paper presents a dataset from a survey of student perceptions and experiences of quality assurance in Vietnamese higher education institutions. Data were collected from July to September 2020 using the online survey via Google Forms. The survey was sent to students via their email and social media, and there were 1323 valid responses. The data collection instrument was developed based on an international survey administered by UNESCO. The survey was designed to elicit data with respect to students’ views on institutional quality policy and model, quality assurance procedures and tools, and student survey. The dataset serves as an insightful reference for institutional practitioners and policymakers in quality assurance to revise internal quality assurance policies and instruments to enhance the quality of teaching and learning. Moreover, the dataset could be of interest to other educational researchers who can use it to investigate students’ understanding and viewpoints on quality assurance.